Biology and management of Bemisia whitefly vectors of cassava virus pandemics in Africa - Legg, James P.; Shirima, R.R.; Tajebe, L.; Guastella, D.; Boniface, S.; Jeremiah, S.; Nsami, E.; Chikoti, Patrick Chiza; Rapisarda, Carmelo (Wiley, 2014)
Cassava mosaic disease and cassava brown streak disease are caused by viruses transmitted by Bemisia tabaci and affect approximately half of all cassava plants in Africa, resulting in annual production losses of more than $US 1 billion. A historical and current bias towards virus rather than vector control means that these diseases continue to spread, and high Bemisia populations threaten future virus spread even if the extant strains and species are controlled. Progress has been made in parts of Africa in replicating some of the successes of integrated Bemisia control programmes in the south-western United States. However, these management efforts, which utilise chemical insecticides that conserve the Bemisia natural enemy fauna, are only suitable for commercial agriculture, which presently excludes most cassava cultivation in Africa. Initiatives to strengthen the control of B. tabaci on cassava in Africa need to be aware of this limitation, and to focus primarily on control methods that are cheap, effective, sustainable and readily disseminated, such as host-plant resistance and biological control. A framework based on the application of force multipliers is proposed as a means of prioritising elements of future Bemisia control strategies for cassava in Africa.